Why animals come together, with the special case of mixed-species bird flocks (2012)
Group living is a widespread, ubiquitous biological phenomenon in the animal kingdom that has attracted considerable attention in many different contexts. The availability of food and the presence of predators represent the two main factors believed to favor group life. In this review, major theories supporting grouping behavior in animals are explored, providing an explanation of animal grouping. This review is divided in two sections. First, major theories as well as potential mechanisms behind the benefit of grouping are described. Later, a special case on the widespread animal social system of mixed-species avian flocks is presented, exploring the available information in relation to the potential causes that bring birds together into this particular social aggregation.